Cognitive decline and hippocampal functional connectivity within older Black adults. Issue 16 (6th September 2022) - Han, S. Duke; Fleischman, Debra A.; Yu, Lei; Poole, Victoria; Lamar, Melissa; Kim, Namhee; Leurgans, Sue E.; Bennett, David A.; Arfanakis, Konstantinos; Barnes, Lisa L.
Abstract: While there has been a proliferation of neuroimaging studies on cognitive decline in older non‐Hispanic White adults, there is a dearth of knowledge regarding neuroimaging correlates of cognitive decline in Black adults. Resting‐state functional neuroimaging approaches may be particularly sensitive to early cognitive decline, but there are no studies that we know of that apply this approach to examining associations of brain function to cognition in older Black adults. We investigated the association of cognitive decline with whole‐brain voxel‐wise functional connectivity to the hippocampus, a key brain region functionally implicated in early Alzheimer's dementia, in 132 older Black adults without dementia participating in the Minority Aging Research Study and Rush Memory and Aging Project, two longitudinal studies of aging that include harmonized annual cognitive assessments and magnetic resonance imaging brain imaging. In models adjusted for demographic factors (age, education, sex), global cognitive decline was associated with functional connectivity of the hippocampus to three clusters in the right and left frontal regions of the dorsolateral prefrontal cortex. In domain‐specific analyses, decline in semantic memory was associated with functional connectivity of the hippocampus to bilateral clusters in the precentral gyrus, and decline in perceptual speed was inversely associated with connectivity of the hippocampus to the bilateral intracalcarine cortex and the right fusiform gyrus. These findings elucidate neurobiological mechanisms underlying cognitive decline in older Black adults and may point to specific targets of intervention for Alzheimer's disease. Abstract : While there has been a proliferation of neuroimaging studies on cognitive decline in older non‐Hispanic White adults, there is a dearth of knowledge regarding neuroimaging correlates of cognitive decline in Black adults who are at particular risk for Alzheimer's disease. In models adjusted for demographic factors (age, education, sex), global cognitive decline was associated with functional connectivity of the hippocampus to three clusters in the right and left frontal regions of the dorsolateral prefrontal cortex. These findings elucidate neurobiological mechanisms underlying cognitive decline in older Black adults and may point to specific targets of intervention for Alzheimer's disease.